The Dialectic of Hadith in Fidyah Tradition in Indramayu - Nurkholis Sofwan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This article describes the dialectic of hadith in fidya tradition in Indramayu. The doctrine of fidya had generated controversies among Muslims in Indramayu, especially the fidya for obligatory daily prayers. However, there are groups of Muslim in Indramayu who believe that fidya is of Islamic teachings a Muslim must observe in his/her daily life. Through observation, interviews, and documentation, also employing the phenomenological and ethnographic perspective, this article gets closer to the tradition and finds that the hadith is seen as a form of iḥtiyāṭ (being careful) with regard to the obligatory prayers and fasting that are yet performed by the death (limited to familial related individuals). This tradition is carried out by giving rice or certain amount of money to the poor, with or without any specific rituals. This brings about some impacts, one of which is the assumption that the tradition serves as a means to help each other, resulting in the fostering of harmony among the society members.